Analysis of Translation Techniques and Quality of Charactonyms in The Silmarillion by J. R. R. Tolkien - Sari, Fibiyola Widya (Jurnal Bahasa, Sastra, dan Studi Amerika, 2023)
The object  of this study is translation of the charactonyms in the book The Silmarillion by J. R. R. Tolkien. This objective of this study is to analyze the techniques used by the translator in translating the charactonyms and the impact of the techniques on the quality of the translation of the charactonyms in terms of accuracy and acceptability. The data are charactonyms found in the book, their translations and the quality assessed with the help of informants. The data were collected using content analysis and focus group discussion. As many as 196 charactonyms from the novel The Silmarillion were discovered and analyzed. This research also unveiled that the translator uses 27 techniques that use six of Fernandes’ (2006) techniques—rendition, copy, addition, transcription, transposition, and deletion—either as single or combined technique, in which 3 techniques are single techniques and 24 are combined techniques. The overall score for the accuracy of the translation is 2.98 and for acceptability is 2.45, making the overall score being 2.72.